What Is Not in the Methods Section: Challenges, Successes, and Lessons Learned From Conducting School-Based Interpersonal Violence Prevention Research - Edwards, Katie M. (Journal of interpersonal violence, 2023)
Interpersonal violence (IV)—which includes sexual assault, sexual harassment, teen dating violence, bullying, and other forms of violence—among youth (i.e., individuals 18 years of age or younger) is a public health crisis in the United States. As such, preventing IV among youth is a public health priority. Schools are natural settings for IV prevention among youth. However, conducting school-based IV prevention research with youth in school settings is riddled with challenges, and there is little systematic discussion of lessons learned from doing this work. As such, the purpose of this paper is to outline challenges, successes, and lessons learned from conducting school-based IV prevention research, as ascertained by four researchers with over 75 years of collective experience conducting school-based IV prevention research. Specifically, we focus on the importance of researchers (1) doing research on the school/school district prior to reaching out about potential partnerships; (2) establishing relationships with school partners that are characterized by being present, trustworthiness, and respect as well as the prioritization of school partners’ ideas over one’s research agenda; (3) working collaboratively with school partners to conceptualize and fund school-driven ideas; (4) preparing for pushback, often from parents/caregivers; and (5) embracing reciprocity (i.e., do things to support your school partners that may not directly benefit you). Additional considerations for recruitment, enrollment, and retention; program implementation and data collection; and dissemination are discussed.